Plasma concentrations of the trace elements copper, zinc and selenium in Brazilian children with autism spectrum disorder - Saldanha Tschinkel, Paula Fabiana; Bjørklund, Geir; Conón, Lourdes Zélia Zanoni; Chirumbolo, Salvatore; Nascimento, Valter Aragão (Biomedicine & pharmacotherapy, 2018)
[Display omitted] [Display omitted] •A cohort of Brazilian children with ASD has been investigated.•ASD children evaluated for plasma level of Cu, Zn, and Se.•Plasma levels of Cu, Zn, and Se were within the reference limits.•A little difference in the level of Mg was reported for males.•Data are preliminary of a wider study for micronutrients in ASD in Brazil. The association between the plasma levels of trace elements, such as copper (Cu), zinc (Zn) and selenium (Se), in people with autism spectrum disorder (ASD), has attracted the interest of many physicians in the very recent years, because the impaired homeostatic regulation of trace elements, including their levels in the bloodstream and their potential neurotoxicity, contribute to the onset and exacerbation of ASD. In this study, we investigated 23 pediatric subjects (≤ 18 yrs old, both sexes) with ASD, all residents in the city of Campo Grande in Brazil, by searching for their micronutrient levels in plasma in relation with metabolic and nutrition biomarkers. Aside for the few evidence reported, generally, the Brazilian cohort of ASD children here examined did not show a marked difference in micro-nutrient intake in relation with their resident geographical area and their dietary habit or metabolic state, although a slight difference in the levels of magnesium and phosphorus was retrieved due to sex difference.